Recollection in the human hippocampal-entorhinal cell circuitry - Bernhard P. Staresina (Nature Portfolio, 2019)
The hippocampus is involved both in episodic memory recall and scene processing. Here, the authors show that hippocampal neurons first process scene cues before coordinating memory-guided pattern completion in adjacent entorhinal cortex.